ANALISIS PENGARUH LINGKUNGAN KERJA FISIK DAN NONFISIK, TERHADAP PRODUKTIVITAS PEGAWAI PADA UNIVERSITAS ISLAM DARUL ULUM LAMONGAN - Ahmad Fathur Rozi; Ahmad Yani Syaikhudin (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2020)
In organizations or human resources, companies are assets that are considered very potential and important. One that makes employees comfortable is the physical and non-physical environment. From this problem can increase productivity. Human resources in this case employees or employees of organizations or companies should not be underestimated. Organizations or companies must provide a special section that is tasked with handling problems relating to employees, that part is called human resource management (HR) or more commonly called the personnel section. Personnel in this case are human resource managers. The manager's scope includes learning and developing ways for employees to effectively devote all their potential and strengths to help achieve the goals of the organization or company. This study uses a quantitative descriptive approach and this study has a population of 260 respondents and a sample of 80 respondents. The data obtained were analyzed through validity test, reliability test, multiple regression analysis, and hypothesis testing with T test, and analysis of the coefficient of determination (R2). This study has physical work environment variables (X1), coloring indicators, cleanliness, lighting, air, spatial planning, and non-physical work environment variables (X2) indicators are supervision, work atmosphere, reward system, good treatment, security of members, and employee productivity variables (Y) the indicators are human, capital, production process, organizational environment, work environment. From the results of the regression analysis it is known that the greatest influence on employee productivity is the non-physical work environment (X2) which has a coefficient of 0.698. Then the next variable is the physical work environment (X1) with a coefficient of 0.203. Hypothesis testing Then from the results of the T test showed that the two independent variables proved to have a significant effect on employee work productivity. In addition, the adjusted R square determination coefficient test of 0.689 shows that 68.9% of variation in employee productivity can be explained by two independent variables in the regression equation. While the remaining 31.1% is explained by other variables beyond the two variables used in this study.